Relations among Glycemic Control, Circulating Endothelial Cells, Nitric Oxide, and Flow Mediated Dilation in Patients with Type 2 Diabetes Mellitus - Kotb, N. A.; Gaber, R.; Salah, W.; Elhendy, A. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Circulating endothelial cells (CEC) have been identified as a surrogate marker of endothelial dysfunction. The aim of this study was to determine the association of glycemic control with CEC and endothelial function in patients with type 2 diabetes mellitus (DM).We studied 30 patients with type 2 DM and 20 age and sex matched healthy controls (HC). Number of circulating endothelial cells was measured by flow cytometry. Endothelial function was studied by measuring flow mediated vasodilation (FMD%) in the brachial artery and serum level of nitric oxide (NO).CEC count was significantly elevated in patients with DM, than HC (35.3±15.1 vs. 7.3±2.4, p<0.001) and in patients with HbA1c>7 than patients with HbA1c≤7 (47.4±5.5 vs. 19.5±5.7, p<0.001). FMD% and NO were lower in DM patients than HC (3.5±0.85 vs. 9.5±3.1, p<0.001 and 37.8±6.1 vs. 64.1±5.7, p<0.001 respectively). FMD% and NO were lower in patients with HbA1c>7 as compared to patients with HA1c≤7 (2.8±0.4 vs. 4.3±0.4, p<0.001 and 33.1±2.9 vs. 43.9±2.8, respectively, p<0.001). HbA1c correlated negatively with FMD% and NO levels and positively with CEC. CEC count correlated negatively with FMD% and NO. There was a significant positive correlation between CEC count and HBA1c (p<0.001 for all correlations).CEC is associated with markers of endothelial dysfunction and disease control in patients with type 2 DM. These findings suggest a potential role of CEC in the pathophysiology of cardiovascular disease in type 2 diabetic and raise the importance of tight glycemic control.
Keywords: circulating endothelial cells; nitric oxide; diabetes mellitus; endothelial function